2019
DOI: 10.1016/j.bbrc.2019.05.105
|View full text |Cite
|
Sign up to set email alerts
|

P311, a novel intrinsically disordered protein, regulates adipocyte development

Abstract: Adipocyte development and adipose tissue expansion have many implications for human diseases, including obesity. Obesity is a debilitating disorder and a risk factor for metabolic disorders including insulin resistance and diabetes mellitus, due in part to an overabundance of adipocytes and adipocyte dysfunction. In recent years, obesity has become a global pandemic with approximately one-third of US adults classified as obese. Adipose tissue has recently been identified as a major metabolic organ, classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Lipid contents in adipocytes were visualized as well as measured using Oil Red-O (ORO) staining (Nunez et al, 2019).…”
Section: Oil Red O Staining: Determination Of Lipid Contentmentioning
confidence: 99%
“…Lipid contents in adipocytes were visualized as well as measured using Oil Red-O (ORO) staining (Nunez et al, 2019).…”
Section: Oil Red O Staining: Determination Of Lipid Contentmentioning
confidence: 99%
“…It has been reported that Ang II reduced adipose conversion by Ang II type 1 receptor, whereas blockade of this receptor markedly enhanced adipogenesis in both human and 3T3-L1 preadipocytes [ 7 , 8 ]. In this study, we also examined the effect of Ang II and its receptor on the expression of key adipogenic markers [ 17 ] such as PPARγ, AP2, C/EBPα, and ACC, during the adipogenic process of 3T3-L1 induced by Ang II. As shown in Figure S3 , Ang II inhibited the expression of adipogenic markers in 3T3-L1 through an AT1 receptor, which is consistent with the previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…The 3T3 L1 preadipocytes were cultured in DMEM and cell viability assays were conducted as previously described [15,16]. Determination of adipocyte lipid content using quantitative Oil Red O staining Lipid contents in adipocytes were visualized as well as measured using Oil Red O (ORO) staining [17,18].…”
Section: Cell Culture and Differentiation Of Adipocytesmentioning
confidence: 99%